The new system of financing science Horizon 2020 as a development opportunity for European and Polish science - Geryk, Marcin (Nowy system finansowania nauki Horyzont 2020 jako szansa rozwoju europejskiej i polskiej nauki, 2016)
The author examines how the strategic objectives of Horizon 2020 are an opportunity for Polish science. The program allocates significant resources to specific tasks such as the implementation of innovation and social challenges. Despite relatively low public expenditure on education, Poland is placed in the European Union average. However, in the case of competitions Horizon 2020 bonus criteria are different from the current Polish finance division algorithm. Emphasis was placed on the relationship between science and the labor market, which in Poland is not significant. These funds will mean a true test of the potential of Polish scientific institutions. In this article the author has analyzed the various opinions of scientific environment in terms of opportunities and threats.
Społeczeństwo i Ekonomia = Society and Economics, 2016, Nr 1 (5), s. 108-117
Keywords: financing of education; EU funds; new technologies; research and development; finansowanie nauki; fundusze unijne; nowe technologie; rozwój